Integration of data in studies of genetic diversity of tomato - Martins, Francielle Alline; Souza Carneiro, Pedro Crescêncio; da Silva, Derly José Henriques; Cruz, Cosme Damião; de Souza Carneiro, José Eustáquio (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to integrate data from quantitative, multicategorical, molecular and phytopathological traits in order to evaluate the genetic diversity of tomato subsamples from the germplasm bank of the Universidade Federal de Viçosa (BGH-UFV). Data from 67 tomato subsamples from BGH-UFV were used, characterized according to 19 quantitative traits, 30 multicategoric characters, 52 ISSR loci, and to the reaction to three diseases (Alternaria solani, Pseudomonas syringae pv. tomato and Tomato yellow spot virus). Initially, the diversity assessment between the subsamples was performed for each set of characters, indicating that diversity based on any one set of data does not reflect the diversity of another set. For the integration of data, the quantitative ones were coded as multicategoric, by five different strategies. The coding strategy with equitable division of the range of data in three classes was the most appropriate, with correlation of 0.78 between the dissimilarity matrices of encoded and original data. The analysis of genetic diversity by the integration of data resulted in groups with higher correspondence to the origins of the subsamples of tomato, indicating that the integration of data from different sources can be successfully carried out by the conversion of quantitative data in multicategoric.